The Role of Nurses in Diabetes Management: Improving Patient Outcomes through Education and Care - Ahlam Abdulkarim Alsuliman; Saleema Saeed Al Akroush; Hanadi Mohammed Jasim Al Dawood; Fatimah Abdulhadi Mohammed Aldawood; Naziha Ali Aloqaili; Rania Hassan Al Urayyidh; Fadia Ali Saleh Almoomen; Tasneem Abdullah Al Zain; Najla Ali Al Sadiq; Yousra Moosa Ali AL Sulais; Laila khalaf Almassry (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Diabetes is chronic and is today being suffered by millions of people across the globe, and the number keeps increasing lesions due to the effects of aging, sedentary lifestyles, and unhealthy eating habits. It is important to manage diabetes in such a way as to avoid the complications associated with it, such as cardiovascular complications, kidney failure, neuropathies, and blindness. Diabetes management involves a team of healthcare professionals, among whom nurses play a pivotal role by improving patient outcomes through direct care, patient education, and continuing support. Aim of work: To explore the crucial role of nurses in the management of diabetes, focusing on how their involvement in patient education, lifestyle support, emotional care, and self-management strategies significantly contributes to improving patient outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Nurses, Diabetes Management, Improving, Patient Outcomes, Education and Care. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:Giving importance to the role of nurses in the management of diabetes has improved the health outcomes of patients. They assist patients to manage their diseases through education, lifestyle changes, emotional support, and continuous care so that they learn how to live with diabetes and avoid further complications. Therefore, collaboration with patients and individualized care allow nurses to assist diabetic patients in creating better, healthier lives. In addition, nurses will have an increasing role in educating patients about self-management and remote monitoring as diabetes management moves into the technological age. Nurses are more than caregivers-they are educators, advocates, and motivators, highly influential in changing the lives of patients with diabetes.